Combined use of fluorescence with a magnetic tracer and dilution effect upon sentinel node localization in a murine model - Kuwahata A (Dove Medical Press, 2018)
Akihiro Kuwahata,1,* Muneer Ahmed,2,* Kohei Saeki,3 Shinichi Chikaki,1 Miki Kaneko,1 Wenqi Qiu,1 Zonghao Xin,1 Shinji Yamaguchi,3 Akiko Kaneko,1 Michael Douek,2 Moriaki Kusakabe,3,4 Masaki Sekino1 1Department of Electrical Engineering and Information Systems, Graduate School of Engineering, The University of Tokyo, Hongo, Bunkyo-ku, Tokyo, Japan; 2Division of Cancer Studies, King’s College London, Guy’s Hospital Campus, Great Maze Pond, London, UK; 3Graduate School of Agriculture and Life Sciences, The University of Tokyo, Hongo, Bunkyo-ku, Tokyo, Japan; 4Matrix Cell Research Institute Inc., Ibaraki, Japan *These authors contributed equally to this work Background: Sentinel node biopsy using radioisotope and blue dye remains a gold standard for axillary staging in breast cancer patients with low axillary burden. However, limitations in the use of radioisotopes have resulted in emergence of novel techniques. This is the first in vivo study to assess the feasibility of combining the two most common novel techniques of using a magnetic tracer and indocyanine green (ICG) fluorescence.Materials and methods: A total of 48 mice were divided into eight groups. Groups 1 and 2, the co-localization groups, received an injection of magnetic tracers (Resovist® and Sienna+®, respectively) and ICG fluorescence; distilled water was used as the solvent of ICG. Groups 3 and 4, the diluted injection groups, received an injection of magnetic tracers (Resovist and Sienna+, respectively) and saline for dilution. Groups 5, 6, and 7, the control groups, received magnetic tracer (Resovist, Sienna+) and ICG alone, respectively. Fluorescent intensity assessment and iron quantification of excised popliteal lymph nodes were performed. Group 1', a co-localization group, received an injection of magnetic tracers (Resovist) and ICG' fluorescence: saline was used as the solvent for ICG.Results: Lymphatic uptake of all tracers was confined to the popliteal nodes only, with co-localization confirmed in all cases and no significant difference in fluorescent intensity or iron content of ex vivo nodes between the groups (except for Group 1'). There was no impact of dilution on the iron content in the diluted Sienna+ group, but it significantly enhanced Resovist uptake (P=0.005). In addition, there was a significant difference in iron content (P=0.003) in Group 1'.Conclusion: The combination of a magnetic tracer (Resovist or Sienna+) and ICG fluorescence is feasible for sentinel node biopsy and will potentially allow for precise transcutaneous node identification, in addition to accurate intraoperative assessment. This radioisotope-free “combined technique” warrants further assessment within a clinical trial. Keywords: sentinel node biopsy, combined technique, fluorescence dye, magnetic nanoparticles, dilutional effect